1993
DOI: 10.1071/ar9931389
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation frequency and nitrogen fertilizers modify cotton yield at Emerald, central Queensland

Abstract: Four irrigation frequencies and six nitrogen (N) fertilizer rates (0-300 kg ha-1) were applied to cotton (Gossypium hirsutum L.) grown on three Vertisols in the Emerald Irrigation Area, central Queensland. The purpose was to describe lint production responses to the plant available water before irrigation and N fertilizer, in terms of the crop N content and the efficiency of crop N use for lint production. Lint yield was greatest when the plant available water before irrigation was 50-80010 of the plant availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…7). This indicates a substantial change over the past two decades where Ockerby et al (1993) and Constable and Rochester (1988) indicated the optimum lint yield was obtained with crop N uptake of only 120-130 kg N/ha, but when lint yield were considerably lower. Current cotton cultivars tend to take up more N (and other nutrients) than has been historically measured, a result of both improved (higher-yielding) cultivars and improved soil fertility (unpublished, Rochester and Constable).…”
Section: Crop Inue Measurementsmentioning
confidence: 92%
“…7). This indicates a substantial change over the past two decades where Ockerby et al (1993) and Constable and Rochester (1988) indicated the optimum lint yield was obtained with crop N uptake of only 120-130 kg N/ha, but when lint yield were considerably lower. Current cotton cultivars tend to take up more N (and other nutrients) than has been historically measured, a result of both improved (higher-yielding) cultivars and improved soil fertility (unpublished, Rochester and Constable).…”
Section: Crop Inue Measurementsmentioning
confidence: 92%
“…6). The LAI values in the growth experiments are typical of those observed in temperate (Constable and Hearn, 1981; Constable et al, 1990) and well managed tropical crops in Australia (Basinski et al, 1975; Ockerby et al, 1993), although high N rates can generate much larger canopies (Basinski et al, 1975; Ockerby et al, 1993). Thus, there is no evidence that ontogenetic changes in SLN grad or k generally contribute to the dynamics of RUE for Australian cotton crops.…”
Section: Discussionmentioning
confidence: 99%